Optimal waist circumference cut-off values for predicting cardiovascular risk factors in a multi-ethnic Malaysian population - Cheong, Kee C.; Ghazali, Sumarni M.; Hock, Lim K.; Yusoff, Ahmad F.; Selvarajah, Sharmini; Haniff, Jamaiyah; Zainuddin, Ahmad Ali; Ying, Chan Y.; Lin, Khor G.; Ab Rahman, Jamalludin; Shahar, Suzana; Mustafa, Amal N. (Asian Oceanian Association for the Study of Obesity, 2013)
Introduction: Previous studies have proposed the lower waist circumference (WC) cutoffs be used for defining abdominal obesity in Asian populations. Objective: To determine the optimal cut-offs of waist circumference (WC) in predicting cardiovascular (CV) risk factors in the multi-ethnic Malaysian population. Methods: We analysed data from 32,703 respondents (14,980 men and 17,723 women) aged 18 years and above who participated in the Third National Health and Morbidity Survey in 2006. Gender-specific logistic regression analyses were used to examine associations between WC and three CV risk factors (diabetes mellitus, hypertension, and hypercholesterolemia). The Receiver Operating Characteristic (ROC) curves were used to determine the cut-off values of WC with optimum sensitivity and specificity for detecting these CV risk factors. Results: The odds ratio for having diabetes mellitus, hypertension, and hypercholesterolemia, or at least one of these risks, increased significantly as the WC cut-off point increased. Optimal WC cut-off values for predicting the presence of diabetes mellitus, hypertension, hypercholesterolemia and at least one of the three CV risk factors varied from 81.4 to 85.5 cm for men and 79.8 to 80.7 cm for women. Conclusions: Our findings indicate that WC cut-offs of 81 cm for men and 80 cm for women are appropriate for defining abdominal obesity and for recommendation to undergo cardiovascular risk screening and weight management in the Malaysian adult population.